IMMERSIVE GOVERNANCE NETWORKS IN THE COVID-19 ERA - Carreón Guillén, Javier; García Lirios, Cruz; Espinoza Morales, Francisco; Bermúdez Ruíz, Gilberto (Revista Educação e Infâncias, 2023)
As of January 2023, the pandemic has claimed the lives of more than four million. Confirmed cases of around a million victims accumulate in Mexico. In this scenario, the Mexican State has escalated into a conflict with Higher Education Institutions for the return to school. While educational policies revolve around the return to classes, even when young people do not have the basic immunization scheme, public universities lead the practice of the virtual classroom. The objective of this work is to analyze and discuss the social representations around the mediation, conciliation and arbitration of the differences between the public administration of education and the autonomy of the universities regarding the return to the traditional classroom. A bibliographic review was carried out considering the link between the policies to mitigate and contain the pandemic in relation to the protocols for returning to face-to-face classes followed by public universities. The results show that the social representations of the conflict between political and academic actors revolve around five dimensions: conflict, negotiation, consensus, self-regulation and co-responsibility. The axes, trajectories and relationships between the nodes that make up the structure of academic governance in the face of the pandemic are highlighted. In relation to the state of the art, the asymmetries between political and educational actors are discussed.